Evaluation of the Quality of Learning Outcomes Reviewed from the Learning Motivation of Students in the Specialization Development Education for Women and Children Criminal Investigators at the National Police Education and Training Center (Lemdiklat Polri) - Wulandari, Adi; Abraham, Irfan (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the role of learning motivation on the quality of learning outcomes in the Specialization Development Education Program for Women and Children Criminal Investigators at the National Police Education and Training Center. Using a qualitative approach with observation techniques, in-depth interviews, and documentation studies, this study found that learning motivation has a significant influence on participants' success in absorbing training materials. The main findings indicate that intrinsic motivation—such as a sense of responsibility, concern for victims, and commitment to duty—is the dominant factor that drives active participant involvement. On the other hand, extrinsic motivation such as institutional incentives and support from superiors act as a booster for learning enthusiasm. A conducive learning environment, contextual teaching methods such as case studies and simulations, and support from instructors and colleagues also strengthen the effect of motivation on learning outcomes. This study confirms the relevance of the Self-Determination theory, learning ecology, and social learning in the context of police education. The results of this study contribute to the design of curriculum, instructor training, and institutional policies that are oriented towards improving the quality of training for police investigators, especially in handling cases of violence against women and children.